Faktor yang berhubungan dengan Praktik Vaginal douching pada Wanita Usia Subur dengan Pendekatan Teori Health Belief Model - Gaharuni Sahika Mutdinia; Retnayu Pradanie; Tiyas Kusumaningrum (Universitas Airlangga, 2019)
Introduction: The practice of vaginal douching is still widely practiced by women of childbearing age without an indication of health. The aim of this research is to know the relationship between factors of vaginal douching practice based on the Health Belief Model Theory among women of child-bearing age.Methods: This research was conducted by using descriptive analytic design with cross sectional approach. Population of this research are women child-bearing age in Gelangan Village. Sample on this research was 169 respondents which were chosen by using cluster sampling technique. Independent variables in this research were perceived of seriousness, perceived of suscepbility, perceived of benefits, perceived of barriers, cues to action and self-efficacy. Dependent variable in this research was vaginal douching practice. The data colleting technique used in this research was questionnaire which was analysed by using Regresi Logistic test with α ≤0,05 level significance.Results: The result showed that perceived benefits (p=0.008) and perceived barriers (p=0.001) were correlated with vaginal douching practice. However, perceived seriousness (p=0.809), perceived suscepbility (p=0.272), cues to action (0.420) and self-efficacy (p=0.228) were not correlated with vaginal douching practice among women child-bearing age.Conclusion: Perceived of high benefits and perceived of low barriers was increased vaginal douching practice among women child-bearing age. However, other components of HBM theory such as perceived seriousness, perceived suscepbility, cues to action and self-efficacy were not related to vaginal douching practice. The next research were expected to explore related modifying factors.